2018
DOI: 10.1063/1.5013074
|View full text |Cite
|
Sign up to set email alerts
|

Pedestal dynamics across low to high confinement regime in the HL-2A tokamak

Abstract: Interactions among pedestal shear flows, turbulence, and the formation of the edge transport barrier have been studied in H-mode plasmas of the HL-2A tokamak by multi-channel Doppler reflectometry with high spatiotemporal resolution. Geodesic acoustic mode (GAM) has been observed during the L-I-H transition. It has been observed that the plasma transits into the I-phase when the mean E×B shear flow reaches a critical value. The bi-spectrum analysis has shown that there is a strong interaction between GAM and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…r /∂r| are negligible [3]. Results on the ASDEX Upgrade also indicated that, in the pedestal region, E r is mainly determined by the ion pressure gradient, when the toroidal flow is negligibly small [6].…”
Section: Overview Of Hl-2a Recent Experimentsmentioning
confidence: 96%
See 1 more Smart Citation
“…r /∂r| are negligible [3]. Results on the ASDEX Upgrade also indicated that, in the pedestal region, E r is mainly determined by the ion pressure gradient, when the toroidal flow is negligibly small [6].…”
Section: Overview Of Hl-2a Recent Experimentsmentioning
confidence: 96%
“…r and E v θ r denote the ion diamagnetic, toroidal velocity and poloidal velocity components of E r , respectively. Whist in p i component, the contribution from ion temperature gradient is dominant over that from density gradient [3].…”
Section: Overview Of Hl-2a Recent Experimentsmentioning
confidence: 99%
“…The negative V θ indicates that the QCM propagates in the electron-diamagnetic drift direction in the laboratory frame. The plasma poloidal rotation at middle of pedestal is estimated to be about V p = 4.5 ~5.2 km s −1 in electron diamagnetic drift direction using the multi-channel Doppler reflectometry [25]. It is noted that the toroidal return flow might have some contributions to the poloidal motion of the mode due to the barber pole effect.…”
Section: Characteristics and The Nonlinear Coupling Of The Pedestal Qcmmentioning
confidence: 99%
“…2017; Liang et al. 2018; Cavedon et al. 2020), the full understanding of the physical mechanism for the enhanced plasma confinement in H-mode operation is an open issue.…”
Section: Introductionmentioning
confidence: 99%